2002
DOI: 10.1186/1471-5945-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Early inflammatory markers in elicitation of allergic contact dermatitis

Abstract: Background: Allergic Contact Dermatitis (ACD) is regarded as a T-cell-mediated delayed-type hypersensitivity reaction. We studied the kinetics of the expression of CS-1 fibronectin, thymus and activation-regulated chemokine (CCL17/ TARC) and different chemokine receptors (CR) in skin biopsies from individuals suffering from back problems, with the antigen responsible of their contact dermatitis and an irrelevant antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…As we have shown previously, the skin biopsies from positive reactions showed signs of hypertrophy and swelling of BECs as well as expression of CS-1 fibronectin and CCL17 starting at 2 and 10 h, respectively [21](table 1). A typical Th1/Tc1 immune response was observed, since the majority of mononuclear cells around dermal BECs expressed the chemokine receptor CXCR3 (mean 63.5% in the positive antigen-challenged site versus 6.3% in the control skin).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…As we have shown previously, the skin biopsies from positive reactions showed signs of hypertrophy and swelling of BECs as well as expression of CS-1 fibronectin and CCL17 starting at 2 and 10 h, respectively [21](table 1). A typical Th1/Tc1 immune response was observed, since the majority of mononuclear cells around dermal BECs expressed the chemokine receptor CXCR3 (mean 63.5% in the positive antigen-challenged site versus 6.3% in the control skin).…”
Section: Resultsmentioning
confidence: 88%
“…We investigated the kinetics of CCL21 expression in skin from patients with ACD, a disease in which the sensitization phase is strongly dependent on LC migration, and where expression of important ligands for integrins and chemokine receptors plays a key role in the skin homing of effector Th1/Tc1 lymphocytes [21, 26, 27]. In this regard, we corroborated our previous finding of early expression on BECs of CS-1 fibronectin and TARC, which was followed by a progressive and significant accumulation of CXCR3+ cells in the positive patch test biopsies, clearly indicating the involvement of a Th1/Tc1 immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Activated T cells release proinflammatory cytokines, which then activate local tissue cells, leading to the characteristic late effector responses at 24-48 hours (16-18). In the elicitation phase, the main effector cells have been demonstrated to be IFN-γ-producing CD8 + Tc1 cells (19-21). Thus, CHS is a prototypic T cell-mediated response.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of asthma the pathogenic role of the CCL17/CCL22-CCR4 axis is still controversial (Pease, 2006), as some reports demonstrate efficient improvement of disease symptoms after CCR4 or CCL17 blockade (Kawasaki et al, 2001;Perros et al, 2009;Vijayanand et al, 2010), whereas others do not ( Chvatchko et al, 2000;Conroy et al, 2003). As already mentioned above, enhanced expression of CCL17 and CCL22 has also been observed in allergic contact dermatitis (Bäumer et al, 2004;Goebeler et al, 2001;Kamsteeg et al, 2010;Martín et al, 2002), and contact hypersensitivity responses were significantly inhibited in CCL17-deficient mice (Alferink et al, 2003). Regarding nonallergic diseases, CCL17 has recently been shown to enhance the formation of artherosclerotic lesions in mice by inhibition of Treg cell expansion (Weber et al, 2011).…”
Section: Implication Of Ccl17 Ccl22 and Ccr4 In Other Diseasesmentioning
confidence: 72%
“…A possible link between skin barrier dysfunction and CCL17 was recently reported by Nakahigashi et al, who showed that CCL17 was able to induce aquaporin-3 in human keratinocytes, which in turn promoted keratinocyte proliferation and disturbed barrier function (Nakahigashi et al, 2010). Whereas elevated levels of CCL17 and CCL22 have also been observed in allergic contact dermatitis (Bäumer et al, 2004;Goebeler et al, 2001;Kamsteeg et al, 2010;Martín et al, 2002;), CCL17/CCL22 expression is not significantly increased in Psoriasis vulgaris (Gros et al, 2009;Kakinuma et al, 2002;Kamsteeg et al, 2010;Uchida et al, 2002). This correlates with the fact that psoriasis is a Th1 dominated disease, whereas Th2-type cytokines and chemokines dominate the initial phase of AD, with a shift to Th1-type cytokines in the chronic phase (Grewe et al, 1998;Fujita et al, 2011).…”
Section: Ccl17 As a Biomarker For Disease Severity In Admentioning
confidence: 98%